2009
DOI: 10.1089/ham.2008.1082
|View full text |Cite
|
Sign up to set email alerts
|

Total Antioxidant Status at High Altitude in Lowlanders and Native Highlanders: Role of Uric Acid

Abstract: Hypobaric hypoxia causes oxidative stress and the antioxidant system of the body plays a vital role in controlling it. Urate contributes up to two-thirds of the antioxidant capacity of human blood. The urate production is catalyzed by xanthine oxidase with a concomitant release of free radicals. This study was designed to appraise the role of urate as an antioxidant at high altitude. The study was conducted on 92 male lowlanders and 66 highlanders after ascent to high altitude at 4560 m. Blood was collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…But, production of UA itself is associated with the generation of free radicals. Our previous study has shown that hypoxia-induced elevated UA does not play any beneficial role in maintaining antioxidant/prooxidant balance and acts as a camouflage to TAS (Sinha et al 2009). In the present study this hypothesis can again be supported by the significant increase in TAS level observed in all the groups after exercise.…”
Section: Discussionmentioning
confidence: 96%
“…But, production of UA itself is associated with the generation of free radicals. Our previous study has shown that hypoxia-induced elevated UA does not play any beneficial role in maintaining antioxidant/prooxidant balance and acts as a camouflage to TAS (Sinha et al 2009). In the present study this hypothesis can again be supported by the significant increase in TAS level observed in all the groups after exercise.…”
Section: Discussionmentioning
confidence: 96%
“…However, we are not the first to observe dissociation between urate and oxidative stress indices, protein carbonyl levels in particular. Clinical studies have revealed higher or unchanged protein carbonyls in patients with high urate, including refractory gout patients (30)(31)(32). Furthermore, urate has the capacity to act as a prooxidant under some circumstances (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, significantly raising serum urate concentration for 2 years was of no benefit in patients with relapsing-remitting multiple sclerosis (51). A positive correlation between plasma urate and PC levels has suggested that urate is ineffective in controlling oxidative stress in some other clinical settings (39,40). Although rare, inherited deficiencies of xanthine oxidase and the Urat1 transporter both cause lifelong hypouricemia, but neither has been associated with neurodegenerative diseases or other chronic illnesses linked to oxidative injury (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The level of carbonyl groups in plasma proteins has been used to assess oxidative stress in various disease states (24,(38)(39)(40). We used a standardized ELISA kit to measure PC levels in plasma obtained before treatment, and 1 wk after the first and fifth doses of pegloticase (Table 3).…”
Section: )mentioning
confidence: 99%